2003
DOI: 10.1093/jat/27.4.221
|View full text |Cite
|
Sign up to set email alerts
|

Acute Nitrobenzene Poisoning with Severe Associated Methemoglobinemia: Identification in Whole Blood by GC—FID and GC-MS

Abstract: A rare fatal case of self-poisoning with nitrobenzene following oral ingestion is reported. On presentation to the hospital, severe methemoglobinemia (70%) was observed in an 82-year-old male who had ingested 250 mL of an unknown substance in the previous 24 h. Methylene blue and exchange transfusion were the therapeutic methods applied in the treatment of the methemoglobinemia. Forty-eight hours after ingestion, a blood sample was collected in ICU and sent to our laboratory. We detected that the blood contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 11 publications
2
28
0
1
Order By: Relevance
“…In case of spectra region falling in range of 1400-1600cm -1 shows presence of peak frequencies 1536cm -1 which indicates the presence of Aromatic nitro compounds (Simple hetero-oxy compounds). The results are supported by the studies undertaken by Martinez et al, (2003).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…In case of spectra region falling in range of 1400-1600cm -1 shows presence of peak frequencies 1536cm -1 which indicates the presence of Aromatic nitro compounds (Simple hetero-oxy compounds). The results are supported by the studies undertaken by Martinez et al, (2003).…”
Section: Resultssupporting
confidence: 78%
“…The studies of Martinez et al, (2003) indicates the association of nitro compounds with flavours of bitter almonds and in our study we found the presence of a peak 1540cm-1 in spectral frequency range of 1400-1600cm -1 which is largely associated with Aliphatic Nitro compounds (Simple hetero-oxy compounds).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Several methods have been reported for the extraction of tricyclic antidepressants from human body fluids by liquid -liquid extraction (LLE) with organic solvents such as hexane/isoamyl alcohol [7,8], diethyl ether [9], methanol [10], or ACN [11,12]; SPE with Bond-Elut TCA [13], Bond-Elut Certify [14,15], or 3M-Empore cartridges [16]; and solid-phase microextraction (SPME) [17,18]; before their analysis by GC [13 -15, 18], GC-MS [9,10], HPLC [7,8,16], HPLC-MS [11], HPLC-MS-MS [12,19], and CE [17].…”
Section: Introductionmentioning
confidence: 99%
“…The main disadvantages of HPLC are the relatively long analysis times and the high acquisition and maintenance costs. Several other methods based on micellar electrokinetic capillary chromatography [9], isotachophoresis [10], gas chromatography-mass spectrometry/nitrogen phosphorus detector [11][12][13][14][15] and UV-vis spectrophotometry [16] have also been described. No assay methods for STR determination are reported in the British, United States and European Union Pharmacopoeias.…”
Section: Introductionmentioning
confidence: 99%